2015
DOI: 10.18276/cej.2015.4-08
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Physical Activity in People with Diabetes

Abstract: abstract. Background: Diabetes mellitus is a chronic disease related to the occurrence of numerous metabolic disorders. Their common feature is hyperglycaemia, caused by insufficient insulin secretion or its malfunction. The World Health Organization states that 346 million people worldwide have diabetes. The studies in adults with type 2 diabetes clearly demonstrate that the change of lifestyle behaviours effectively improves glycemic control. The modifications of lifestyle habits, such as regular physical ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Men have a higher physical activity level compared to their female counterparts. 7,11,33 The same pattern has been found in the general population. 36 The difference in PAL between men and women might be because of the difference in social obligations between them; men are expected to be masculine as breadwinners, while women are usually restricted around the house.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Men have a higher physical activity level compared to their female counterparts. 7,11,33 The same pattern has been found in the general population. 36 The difference in PAL between men and women might be because of the difference in social obligations between them; men are expected to be masculine as breadwinners, while women are usually restricted around the house.…”
Section: Discussionsupporting
confidence: 78%
“…9,34 On the contrary, some studies have revealed that those with high BMI have high PAL because of their understanding of the effect of weight on diabetes mellitus. 4,7…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations